Secteur semencier au Burkina Faso : Recommandations pour une meilleure integration des producteurs - Djamen, Patrice; Outtara, Souleymane (2017)
This report presents the results of an analysis of the seed sector in Burkina Faso focusing on the issues that affect smallholder farmers' abilities to participate in such sector and benefit from it. It provides recommendations for different actors (from regulators to seed enterprises, extension agents, non-govermental organizations and farmers themselves) to address these issues and consequently contribute to a more integrated and pluralistic seed sector. The study that led to this report was conducted under the project "Improving Seed Systems for Smallholder Farmers' Food Security", funded by Swiss Development and Cooperation (SDC) and implemeneted in Bolivia, Burkina Faso, Nepal, Uganda and Uzbekistan. Policy and legal analyses, literature reviews, interviews with experts and a roundtable with key informants were included in the study.